Rural development, population aging and gender in Spain: the case of rural women in the autonomous community of Castilla y León - Jesús María Gómez García; Margarita Rico González (European Regional Science Association (ERSA), 2004)
The transformation that rural areas have undergone during the last 30 years constitutes a very important phenomenon in Spain, but it is especially relevant in certain regions such as the Autonomous Community of Castilla y León. The constant process of depopulation, which a great number of villages of that region are suffering, primarily caused by the continuous transfer of labour force from agriculture activities to the industrial sector and, more recently, towards the service sector of urban areas, is provoking the progressive demographic and economic decadence of rural areas. In this context, women played a key role in the process of rural exodus, especially in the case of young women. This trend has created highly aged, male rural populations, with few potential human resources, which are incapable of sustaining and promoting economic and social development in the future. This project attempts to determine to which extent women have been and continue to be the protagonists of the social and economic transformations which have affected rural areas during the last decades. To this aim, we will undertake an analysis by sex of different demographic, economic and social variables at the municipal level, which will show women's spatial situation, according to rural criteria. We will also undertake a prospective analysis of the population evolution of these rural areas, in order to obtain a probable demographic scenario which rural women will have to face in the future. The specific focus of this study will be the territory of the Autonomous Community of Castilla y León. The results of this analysis will serve as a very useful reference for the public authorities as well as for private agents of this and other Spanish regions whenever they have to design alternative policies and actions regarding the role that rural women play and will play in the economic maintenance and development of rural areas. This is especially true given that, until now, studies which focus on the quantitative analysis of the economic and social situation of rural women have been practically nonexistent.
Keywords: 330